O crime de trabalho escravo contemporâneo em face do ordenamento jurídico brasileiro - Helene, Mariana Vieira (2019)
In “The crime of contemporary slave labor towards the Brazilian legal system”, it was necessary to consider that for an eradication of slave labor in Brazil to occur there is a need for change on legal and social reforms regarding both employers and employees. The way capitalism has grown in Brazil, as well as in others third world countries, it has been erratic and reached an unprepared and fragile society, especially when we are dealing with a country that has had for a long time officially enslaved its workers and manual labor has always been undervalued. There are many initiatives to combat this situation, but there is still a great legal difficulty regarding the penal sanctions applied to the practice of slave labor in Brazil, such as the low number of criminal convictions in comparison to the number of people rescued for being in a condition similar to a slave. The purpose of the research lies precisely in the sanctions that can be given to this type of crime, within our current legal system, as well as in the investigation of social policies that may be effective in preventing slave labor in Brazil. In order to carry out the research with the proper depth and importance of the matter, we encountered social rights infringements, social economic issues relating to the worker’s contemporary slave labor position, in addition to historical facts that influenced the perpetuation of this type of crime. The analysis of the crime of reducing a person to a condition analogous to a slave was done from the perspective of the victim, not the defendant, due to its undeniable social vulnerability